2007
DOI: 10.1364/ao.47.000064
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-linewidth megahertz-repetition-rate optical parametric oscillator for high-speed flow and combustion diagnostics

Abstract: We demonstrate the ability to generate ultra-high-frequency sequences of broadly wavelength-tunable, highintensity laser pulses using a custom-built optical parametric oscillator pumped by the thirdharmonic output of a "burst-mode" Nd:YAG laser. Burst sequences consisting of 6-10 pulses separated in time by 6-10 Îs are obtained, with average total conversion efficiency from the 355 nm pump to the near-IR signal and idler wavelengths of 33%. Typical individual pulse output energy for the signal and idler beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…For this work, the purpose of the PCM is to both improve the on/off contrast of the pulse slicer and to limit ASE in the forward direction. Fluorinert FC-75, which has been used extensively as an SBS fluid [18] and has previously performed well when operating the burst mode laser at less than ~250 kHz [18], was used for this work.…”
Section: Laser System Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this work, the purpose of the PCM is to both improve the on/off contrast of the pulse slicer and to limit ASE in the forward direction. Fluorinert FC-75, which has been used extensively as an SBS fluid [18] and has previously performed well when operating the burst mode laser at less than ~250 kHz [18], was used for this work.…”
Section: Laser System Descriptionmentioning
confidence: 99%
“…Note that the trace was obtained with a relatively low sampling rate oscilloscope that required the detector output to be deliberately broadened in time (using a load resistor and the intrinsic cable capacitance). For spectrally narrowed imaging the OPO was operated with injection seeding [18] using an external cavity diode laser (ECDL) manufactured by Sacher, Inc. The OPO "idler" beam is seeded, which results in line-narrowed output for both the idler and signal waves.…”
Section: Laser System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorinert FC-75, which has been used extensively as an SBS fluid [13] was previously found to perform well when operating the burst mode laser at less than ~250 kHz [4]. However, it was found that operation at frequencies of 500 kHz or higher resulted in poor stability and burst uniformity, indicating, presumably, that the system was being operated at, or near, the SBS threshold [12].…”
Section: Laser System Descriptionmentioning
confidence: 99%
“…More recently, solid-state diode-pumped/dye laser technology appears capable of achieving up to 10 kHz of continuous PLIF imaging, but this is still much lower than the bandwidth required for tracking flow phenomena in hypersonic flows [3]. To address this diagnostic need we have been developing, over the last several years, an ultra-high frame rate PLIF imaging system which combines a "burst mode" Nd:YAG-based tunable OPO system [4][5][6], with a framing ICCD camera. In this paper we will demonstrate the utility of the system for obtaining time correlated PLIF movie sequences in a large scale flow facility, the NASA Langley 31" Mach 10 Hypersonic Wind Tunnel [7].…”
Section: Introductionmentioning
confidence: 99%